Clinical, Laboratory, Instrumental, Anamnestic Characteristics in Children With Type I Diabetes Mellitus and Early Stage of Diabetic Nephropathy - Ievgeniia A. Burlaka MD, PhD; Inga O. Mityuryayeva MD, PhD; Tetiana A. Shevchenko MD, PhD; Anastasiia D. Holoborodko; Ihor V. Kovalchuk MD; Lilia O. Lantukh MD (SAGE Publishing, 2021)
Type 1 diabetes (T1D) is mainly a disease of children and young adults. Diabetic nephropathy (DN) is a common finding in diabetic patients. Microalbuminuria is the earliest clinical evidence of DN. Aim of the study was analysis of clinical, laboratory, instrumental, anamnestic examinations data in pediatric patients with T1D and early stage of DN in order to evaluate possible factors associated with early stage of DN and predictors of DN development and progression. A survey of 105 children (62 males, 43 females) with T1D and DN aged 5 to 17 years in Endocrinology unit on Clinical Pediatric Hospital №6 (Kyiv, Ukraine) done. Following clinical and biochemical characteristics found associated with an early DN: inflammatory phenotype (increased ESR, decreased albumin/globulin ratio), functional cardiovascular disorders (increased systolic blood pressure, "minor" ECG changes), signs of secondary metabolic disorders (high HbA1c, increased serum cholesterol level, increase ALAT and ASAT levels). Kidney function impairment at early stage of DN shows: higher MAU grade, GFR decline, rise in serum creatinine level as compared to T1D group. Presence of concomitant kidney and endocrine disease; positive family history found in a bigger number of patients with DN. DKA episodes number found as a factor associated with higher levels of MAU in children with DN. Patients who had microalbuminuria and more than 5 episodes of DKA/year (poorly controlled T1D) have higher progression rate to macroalbuminuria as compared to those who have less than 5 episodes of DKA/year after a 6-year follow-up study.